A strategy to build community empowerment to support independent and sustainable active case finding tuberculosis movement - Argyo Demartotoa; Shubuha Pilar Naredia; Siti Zunariyah; Trisni Utami; Rahesli Humsona; Akhmad Ramdhon; Yuyun Sunesti (Journal of Community Service and Empowerment, 2025)
Tuberculosis (TB) remains a public health challenge in Indonesia, requiring a strategic and innovative approach to address it. This study discusses the TB education strategy through the independent and sustainable Active Case Finding (ACF) method by empowering cadres from the Mentari Sehat Indonesia Foundation (MSI) and Sebelas Maret University (UNS). This collaboration emphasizes the importance of integrating community and academic capacity to systematically increase awareness and early detection of TB. This approach is analyzed through the lens of Paul Virilio's dromology theory, which explains how the speed of information distribution, especially through digital technology, affects the effectiveness of health campaigns and education. This study is a qualitative study using a case study approach. Data were obtained from interviews and direct observations. Data validity used source triangulation. The results of the study show that the success of this strategy was driven by institutional support, multi-sector collaboration, and the use of digital media. However, there are obstacles in the form of social stigma of TB, low health literacy, and disparities in access to technology in vulnerable communities. Through dromology theory, the acceleration of information in public TB campaigns can be optimized to form collective awareness and behavioral change. Education based on cadre empowerment has also been shown to strengthen the sustainability of programs at the local level. Thus, innovation strategies through digital campaigns can become a TB education model that is adaptive, inclusive, and long-term sustainable.